Macroeconomic propagation under different regulatory regimes: Evidence from an estimated DSGE model for the euro area - Matthieu Darracq Pariès; Christoffer Kok; Diego Rodriguez-Palenzuela (European Central Bank (ECB), 2010)
The financial crisis clearly illuminated the potential amplifying role of financial factors on macroeconomic developments. Indeed, the heavy impairments of banks' balance sheets brought to the fore the banking sector's ability to provide a smooth flow of credit to the real economy. However, most existing structural macroeconomic models fail to take into account the crucial role of banks' balance sheet adjustment in the propagation of shocks to the economy. This paper contributes to fill this gap, analyzing the role of credit market frictions in business cycle fluctuations and in the transmission of monetary policy. We estimate a closed-economy dynamic stochastic general equilibrium (DSGE) model for the euro area with financially-constrained households and firms and embedding an oligopolistic banking sector facing capital constraints. Using this setup we examine the macroeconomic implications of various financial frictions on the supply and demand of credit, and in particular we assess the effects of introducing risk-sensitive and more stringent capital requirements. Finally, we explore the scope for counter-cyclical bank capital rules and the strategic complementarities between macro-prudential tools and monetary policy.
Keywords: E4; E5; F4; 330; banking; Bayesian estimation; DSGE Models; financial regulation